Temperature and thermal stress distribution in concrete arch dams in operation - Meri, Tony Carlos (Department of Civil Engineering, 2015)
The temperature field of concrete dams in operational stages is dominantly influenced by variations in environmental seasonal temperature and climatic conditions. Cyclic seasonal temperature and associated thermally induced stresses have been found to contribute significantly to long term degradation of strength and stiffness of concrete dams raising concerns about their durability (Leger et al. 1993). In this study, a critical review of the current state-of-the-art of temperature models for determining temperature distribution including the main environmental parameters influencing the temperature distribution for concrete dams in operation has been undertaken. It is found that, the heat flow in the concrete dams currently is approximated as conduction only and the classical Fourier heat conduction models are adopted as the governing equations to define heat flow mechanisms in the dam. The solution to Fourier heat models is accurately achieved through the finite element analysis using finite element models of the dam to the determine the temperature field.